Escola e cidadania: balanço das concepções expressas pelas dissertações e teses das universidades brasileiras - Cavalcante, Vanessa Luiz (2012)
In this project it is intended to develop a survey that aims to raise and analyze the concepts about the relationship between school and citizenship. These concepts were brought up by the educational research, and expressed by dissertations and thesis in the Brazilian Graduate Programs. The dissertations and the thesis were chosen based on the fact that they are accessible to a possible development of a master's thesis, and because if these productions cannot be classified as high-end work, they express the production of the Brasilian Graduate Programs that can be considered as the locus of the most advanced social research in the country. The analysis of the content has been employed as the procedure for the analysis of research to demonstrate the subjects pointed out in the work. It is based on the contributions of Marshall (1967), Bobbio (2004), Castilho (2011), Arendt (2009), Carvalho (2011), and other authors that use research in education with the focus on the concept of citizenship. Sacristán (2000; 2002) and Gentili (1998; 2001). Intend to make in-depth balance with review of research involving school-citizenship through the following indicators: the concept of citizenship, and school-citizenship